2019
DOI: 10.1126/sciimmunol.aay6039
|View full text |Cite
|
Sign up to set email alerts
|

A divergent transcriptional landscape underpins the development and functional branching of MAIT cells

Abstract: MR1-restricted mucosal-associated invariant T (MAIT) cells play a unique role in the immune system. These cells develop intrathymically through a three-stage process, but the events that regulate this are largely unknown. Here, using bulk and single-cell RNA sequencing–based transcriptomic analysis in mice and humans, we studied the changing transcriptional landscape that accompanies transition through each stage. Many transcripts were sharply modulated during MAIT cell development, including SLAM (signaling l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(126 citation statements)
references
References 67 publications
14
112
0
Order By: Relevance
“…MAIT cells develop intrathymically through a three-stage process in mice and humans. At stage 3, which resembles mature MAIT cells in peripheral organs, the intrathymical MAIT cells comprise two functionally different subpopulations: MAIT1 cells, positive for T-bet and IFN-γ, and MAIT17 cells characterized by RORγt and IL-17 expression [49,50]. Similar to Tc17 cells, MAIT1 and MAIT17 cells contribute to protection against pathogens by secretion of cytokines including IL-17 and IFN-γ in mice and humans.…”
Section: Tc17 Versus Mait and γδ17 T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…MAIT cells develop intrathymically through a three-stage process in mice and humans. At stage 3, which resembles mature MAIT cells in peripheral organs, the intrathymical MAIT cells comprise two functionally different subpopulations: MAIT1 cells, positive for T-bet and IFN-γ, and MAIT17 cells characterized by RORγt and IL-17 expression [49,50]. Similar to Tc17 cells, MAIT1 and MAIT17 cells contribute to protection against pathogens by secretion of cytokines including IL-17 and IFN-γ in mice and humans.…”
Section: Tc17 Versus Mait and γδ17 T Cellsmentioning
confidence: 99%
“…for MAIT1 [50,51] In humans: CD3 + TCRα7. [54,55] Localization at steady state Very rare in SPF-bred WT mice [10,36] Lamina propria [57] Lamina propria, barrier tissues, peripheral blood, liver [51] Thymus, secondary lymphoid organs, barrier tissues [54] Reported protective functions Skin homeostasis detected CD3 +…”
Section: Tc17 Versus Mait and γδ17 T Cellsmentioning
confidence: 99%
“…Naïve RM tended to have lower MAIT cells in blood (∼0.53%), spleen (∼0.90%), and lung (∼1.09%) compared to the rectum (∼2.3%, mean) and liver (∼9.8%, mean) ( Figure 1D). A key feature of the MAIT cell developmental pathway is the expression of PLZF, and cells have been shown to express the transcription factor PLZF in humans and mice (3,6,28,29); thus, we further characterized the macaque CD8 + CD161 ++ TCR7.2 + cells for the expression of PLZF. We observed that the majority of macaque blood CD161 ++ TCR7.2 + CD8 + cells express PLZF ( Figure 1E).…”
Section: Identification Of Mait Cells Using Tcr72 Cd161 and Mr1 Tementioning
confidence: 99%
“…Interestingly, cytolytic proteins are differentially expressed during the development of human MAIT cells, with the mature subsets expressing more of these effector proteins [44]. In adult human female genital tract, oral mucosa, and placental tissues, MAIT cells express low level of GrzB at steady state [12,[45][46][47], suggesting that the regulation of cytolytic effector proteins in tissues may differ from that of blood MAIT cells.…”
Section: Discussionmentioning
confidence: 99%